Islamic Quality of Life and Difficulties in Emotion Regulation as Predictors of Marital Intimacy - Atefeh Nezhad Mohamad Nameghi; Masoumeh Safari (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2026)
Marital intimacy is one of the fundamental pillars of family stability in Muslim societies, particularly in large families that face multiple economic, emotional, and parenting challenges. The present study aimed to examine the role of difficulties in emotion regulation and Islamic quality of life in predicting marital intimacy among large Muslim families with more than four children. This applied study employed a descriptive–correlational design. The statistical population consisted of parents with more than four children who resided in Abyek County in 2025. A total of 120 participants were recruited using convenience sampling. Data were collected using the Marital Intimacy Questionnaire (Bagarozzi, 2001), the Difficulties in Emotion Regulation Scale (Gratz & Roemer, 2004), and the Islamic Quality of Life Questionnaire (Nezhadmohamad Nameghi et al., 2019). Data were analyzed using Pearson correlation coefficients and multiple regression analysis. The results indicated that difficulties in emotion regulation had a significant negative relationship with marital intimacy, whereas Islamic quality of life showed a significant positive relationship with marital intimacy. The regression model revealed that these two variables jointly explained 36% of the variance in marital intimacy. The findings suggest that marital intimacy in large Muslim families emerges from the interaction between emotion regulation skills and spiritual–cultural resources grounded in an Islamic lifestyle. These results highlight the distinctiveness of the Islamic model of well-being compared to secular models and may contribute to the development of family-oriented policies and programs aimed at strengthening marital intimacy in Muslim societies.